Bacterial Infection in Liver Cirrhosis - Rika Bur; Rino A. Gani (The Indonesian Society for Digestive Endoscopy, 2002)
Patients with liver cirrhosis frequently have infection which can deteriorate further the already impaired liver function. The most common form of infection in this particular patients are spontaneous bacterial peritonitis, urinary tract infection, and respiratory infection. Causative organism mostly Gram negative micro organism and originate from the gastrointestinal tract. The weaken of immune defense mechanism and also the altered gastrointestinal tract motility can explained most of these infection. This paper will review the bacterial infection in liver cirrhosis with some guidance in the management. Key words: Liver cirrhosis, spontaneous bacterial peritonitis, systemic antibiotic treatment